Effects of acute caffeine ingestion on the physical performance of amateur American football athletes - Carvalho, Felipe (2024)
The aim of this study was to investigate the effects of acute caffeine ingestion (5 mg.kg-1) on jump, isometric strength and repeated sprint performance in amateur American football athletes. Twelve players (24.6 ± 3.66 years and 115.18 ± 24.35 kg of body weight) ingested a dose of caffeine (5 mg.kg−1) or placebo 60 min prior to a testing session consisting of: 1) countermovement jump (CMJ); 2) isometric mid-tight pull (IMTP); and 3) 3-line drills (200-yd shuttle runs with a 2-minute rest between sprints). Two testing sessions were performed using a double-blind, counterbalanced, crossover design during a pre-season training camp. Results indicated: Caffeine ingestion improved CMJ performance (p = 0.035), but no differences were observed on IMTP strength (p = 0.22) and line drill performance (total time: p = 0.65, and fatigue (%): p = 0.75) when compared to placebo condition. Conclusion: Acute caffeine ingestion improved jump performance, but not isometric strength and repeated sprint with change-of-direction performance in amateur American Football athletes.